Os espaços de transmissão da hanseníase: domicílio, trabalho e relações de vizinhança - Madeira, Elizabeth Santos (2006)
In the Espírito Santo State, in the southeast region of Brazil, prevalence rates of leprosy are decreasing while the detection rates is not. This fact demonstrates that, albeit the quality of services has improved considerably through the years, they still have not been able to affect leprosys’s cycle of transmission in the population. Therefore, there is a need for more effective interventions. The purpose of this study is to analyze the three most common environments for leprosy transmission: the home, the workplace, and neighborhood contacts. In order to accomplish these objectivies, the study was performed in two segments: spacial and exploratory. In the spacial approach, an area of distribution of leprosy cases was performed in the city of Vitória, to calculate the detection rates, and the detection rate among children under 15 years old, in each health care territory of the region. In the exploratory phase of the study, the work environment was investigated, performing an awareness of the modes of transmission, recognition of symptoms, and performing health tests of at risk individuals. In the spacial phase of the study, a comparison was made between two groups of patients: from the urban and rural zone. This study analyzed the contribution of the workplace factor in leprosy transmission. The study of the social contacts showed that the disease is spread in all areas of Vitória, with more concentration in the following regions: Grande São Pedro, the boundaries of São Pedro V, Resistência, and Santo André. This region concentrates 32.5% of leprosy cases in Vitória. Another concentration zone is the neighborhood area of Maria Ortiz and Jabour, in the Continental region. These are places of recent ocupation in the Vitória Island (1980-1990) sharing the same history of migratory invasion. Those migrants placed themselves in “palafitas” precarious wood slums on recovered sanitary land areas. The detection average figures showed that the areas of higher risk for leprosy transmission are four hyper-endemic territories (detection figures - > 10/10.000 inhabitants) where 8.9% of the population subsists, with an average ratio of 33.96% of leprosy cases in Vitória: São Pedro V, Resistência, Santo André e Jabour. The comparison contrast between rates of social deprivation and leprosy suggests a connection between this illness and precarious socio-economic conditions. The study of the patients’ profile showed predominance of middle-aged women who have been living in Vitória over five years, with low socio-economic condition. Also, they are mostly paucibacillary patients, with easy access to health services. The average age of 39 years and 6 months suggests long periods of incubation and explains the difficulties found by the Health Personnel in identifying the sources of infection and developing effective actions to control leprosy. In the analyses of cases realized in the work environment, three new cases were identified at the same place, which demonstrates the relevance of this approach. The comparison between urban and rural groups showed statistically significant differences were found in the detection figures, due to the discovery of cases (through health tests), higher in the urban than the rural group used as control. This fact should explain the high contribution of the household transmission, here characterized by family and neighbors as well, in the phenomenon of likelihood of the presence of the illness in several members of the same family. This may be a consequence of the accelerated urbanization of Espírito Santo in recent decades, which created slums in the peripheries of the big cities characterized by several families related by blood and tightly connected, sharing the same backyards and relating to each other and to other individuals in many possible places of transmission. Altogether, the results suggest that poverty and the consequent sharing of exiguous spaces constitute an important link in leprosy causes. Furthermore, in Vitória, many low-risk individuals are creating more cases than the few high-risk individuals. The study also suggests that strategies towards population and health professionals have been more effective in discovering new cases than the contact exams performed periodically by the Health Departments regulated by the Brazilian Federal Ministério da Saúde. Although a very important measure in the war against the disease, this traditional practice should not be the only one used to detect new cases.